Stem Cell Therapy for Liver Diseases: Current Perspectives - Jing Wang; Qun Li; Wenbo Li; Nahum Méndez-Sánchez; Xiaofeng Liu; Xingshun Qi (Frontiers in Bioscience-Landmark, 2023)
Stem cell therapy offers a promising avenue for advanced liver disease cases as an alternative to liver transplantation. Clinical studies are underway to explore the potential of stem cells from various sources in treating different liver diseases. However, due to the variability among current studies, further validation is needed to ensure the safety and effectiveness of stem cell therapy. To establish a strong foundation for optimal stem cell therapy applications, selection of suitable stem cell sources, standardization of transplantation protocols, and patient criteria are vital. This review comprehensively examines existing literature on stem cell sources, transplantation methods, and patient selection. Additionally, we discuss novel strategies, including stem cell preconditioning, cell-free therapy, genetic modification of stem cells, and the use of liver organoids, addressing the limitations of current stem cell therapies. Nevertheless, these innovative approaches require further validation.